TEKNIK MEMBUAT NILAI SEMESTER MENGGUNAKAN MICROSOFT EXCEL - Ibnu Ziad; Rita Martini; Gusti Ayu Oka Windarti (Politeknik Negeri Sriwijaya, 2019)
Making semester scores using the Microsoft Excel program aims to help lecturers or teachers in making semester grades for students, and the results are more rigorous than manually made. Our goal in conducting this research is to provide knowledge to the lecturers or teachers, and also to know where to use this Microsoft Excel program. The method or approach to the lecturers and teachers is to hold information to them. And from the results of our research or counseling, it turned out that they were very enthusiastic, and they have not known that the Microsoft Excel program can be used to make semester grades for students.